Hypoprolactinemia and hyperprolactinemia in male schizophrenia patients treated with aripiprazole and risperidone and their relationships with testosterone levels - Minami Tasaki; Norio Yasui‐Furukori; Saaya Yokoyama; Masataka Shinozaki; Norio Sugawara; Kazutaka Shimoda (Wiley, 2021)
Abstract Aim Several reports have shown that risperidone increases prolactin concentrations, while aripiprazole decreases prolactin concentrations. The frequency of abnormal prolactin concentrations in patients with schizophrenia receiving these drugs is still unknown. Furthermore, although hyperprolactinemia leads to sexual dysfunction, the relationship between hyperprolactinemia and testosterone, which may be directly related to male sexual function, is not well understood. Methods The subjects were 94 male schizophrenia outpatients receiving risperidone or paliperidone (risperidone group) and 83 male schizophrenia outpatients receiving aripiprazole. We measured the serum prolactin and total and free testosterone concentrations. We compared the prolactin and testosterone levels in patients receiving risperidone or paliperidone and patients receiving aripiprazole. Results The average serum prolactin concentration was 27.5 ± 13.1 ng/mL for the risperidone group and 3.9 ± 3.5 ng/mL for the aripiprazole group, and the concentrations were significantly different (P < .001). Hypoprolactinemia was observed in 75% of the aripiprazole group and hyperprolactinemia in 65% of the risperidone group. A positive correlation between prolactin levels and the risperidone daily dose was found, whereas a negative correlation between prolactin levels and the aripiprazole daily dose was observed. In the risperidone group, total testosterone concentrations were correlated with age, while free testosterone concentrations were inversely correlated with age and prolactin levels. Conclusion We found very common hyperprolactinemia and hypoprolactinemia in the risperidone or paliperidone group and aripiprazole group, respectively. Testosterone concentrations were associated with elevated prolactin levels in patients receiving risperidone or paliperidone. Further studies are needed to determine the clinical relevance of abnormal prolactin concentrations in male and female patients with schizophrenia.